2022
DOI: 10.3346/jkms.2022.37.e1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Premature Mortality Statistics of Autism Spectrum Disorder Among Children in Korea: A Nationwide Population-Based Birth Cohort Study

Abstract: Background The aim of this study was to estimate the 8-year prevalence and mortality statistics of autism spectrum disorder (ASD) according to birth year (2002–2012). Methods We used the National Health Insurance Service database with 4,989,351 children born from 2002 to 2012 including 35,529 children diagnosed with ASD until 8 years of age. The 8-year cumulative prevalence of ASD was calculated annually (2010–2020) with 8 years of follow-up. The 8-year mortality was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Распространенность РАС составляла 1,70 и 1,85% у детей в США в возрасте 4 и 8 лет соответственно, в Европе колебалась от 0,38 до 1,55%, в Израиле -4,8%; в Исландии -3,13%; в США -1,7%; в Катаре -1,14%; в Иране -0,06% [4][5][6][7][8][9][10]. В Южной Корее распространенность РАС была в 2,7 раза выше среди мальчиков (13,5 на 1000 рождений), чем у девочек (5,0 на 1000 рождений), а также из 467360 детей, родившихся в 2012 г., у 9,4 на 1000 рождений был диаг-ностирован РАС до 2020 г. Риск смертности от всех причин был выше среди детей с РАС, и значительно выше среди девочек [11]. В Китае распространенность РАС среди детей 6-12 лет составил 0,70%, где у мальчиков (0,95%) был выше, чем у девочек (0,30%; P <0,001), из 363 подтвержденных случаев РАС 43,3% были впервые диагностированы, и большинство из них (90,4%) посещали обычные школы, а 68,8% детей с РАС имели как минимум одно сопутствующее нейропсихиатрическое заболевание [12].…”
Section: Discussionunclassified
“…Распространенность РАС составляла 1,70 и 1,85% у детей в США в возрасте 4 и 8 лет соответственно, в Европе колебалась от 0,38 до 1,55%, в Израиле -4,8%; в Исландии -3,13%; в США -1,7%; в Катаре -1,14%; в Иране -0,06% [4][5][6][7][8][9][10]. В Южной Корее распространенность РАС была в 2,7 раза выше среди мальчиков (13,5 на 1000 рождений), чем у девочек (5,0 на 1000 рождений), а также из 467360 детей, родившихся в 2012 г., у 9,4 на 1000 рождений был диаг-ностирован РАС до 2020 г. Риск смертности от всех причин был выше среди детей с РАС, и значительно выше среди девочек [11]. В Китае распространенность РАС среди детей 6-12 лет составил 0,70%, где у мальчиков (0,95%) был выше, чем у девочек (0,30%; P <0,001), из 363 подтвержденных случаев РАС 43,3% были впервые диагностированы, и большинство из них (90,4%) посещали обычные школы, а 68,8% детей с РАС имели как минимум одно сопутствующее нейропсихиатрическое заболевание [12].…”
Section: Discussionunclassified
“…Comorbidity in ASD is the rule rather than the exception and may explain the higher risk of premature mortality in autistic individuals, compared to the general population [21][22][23] . The most commonly reported ASD comorbidities are NDDs, epilepsy, cerebral palsy, sleep disorders, psychiatric disorders (anxiety, depression, obsessive-compulsive disorder, psychotic disorders, substance use disorders, oppositional defiant disorder, eating disorders, personality disorders), and general medical conditions (gastrointestinal problems, immune dysregulation, genetic syndromes) 24,25. The plausibility of ASD and migraine comorbidity may be grounded in important common features, as follows: both are chronic prevalent disorders, affecting 2 and 10% of children and adolescents worldwide, respectively 19,26,27 ; they share some pathophysiological changes (neurotransmission dysregulation, especially of the serotoninergic system 28 ; altered immune response causing neurogenic neuroinflammation 29 ; abnormal findings especially in the cortical minicolumn organization 30 ; and dysfunctions in the gut-brain axis 31,32 ) 33 ; susceptibility genes (including calcium channel mutations and polymorphisms 34,35 ); and atypical sensory processing 36 .…”
Section: Discussionmentioning
confidence: 99%
“… 23 A previous study showed that the mortality rate associated with ASD increased across all income classes. 20 Another study found no difference in the income of the family concerning ASD mortality. 21 Thus we decided to consider income class as a confounding factor.…”
Section: Introductionmentioning
confidence: 97%